Comparative pharmacological characterization of D1-like dopamine receptors from Anopheles gambiae, Aedes aegypti and Culex quinquefasciatus suggests pleiotropic signaling in mosquito vector lineages. Issue 1 (December 2016) - Hill, Catherine; Doyle, Trevor; Nuss, Andrew; Ejendal, Karin; Meyer, Jason; Watts, Val
Abstract Background Small molecule antagonists of mosquito dopamine receptors (DARs) are under investigation as a new class of vector-selective insecticides. Antagonists that inhibit the D1 -like DARsAa DOP2 andCq DOP2 from the mosquitoesAedes aegypti L. andCulex quinquefasciatus Say, respectively, also cause larval mortality in bioassays. Here, we report on the orthologous DAR, Ag DOP2, from the malaria mosquitoAnopheles gambiae Giles that was cloned and pharmacologically characterized in HEK293 cells. Larval bioassays were then conducted to examine the potential of DAR antagonist insecticides againstAnopheles vectors. Findings Previous in vitro cAMP accumulation assays demonstrated Gαs coupling forAa DOP2 andCq DOP2 and dose-dependent inhibition by DAR antagonists. We observed a negligible response ofAg DOP2 in the cAMP assay, which prompted an investigation of alternative coupling for mosquito DARs. In an in vitro IP-One Gαq second messenger assay of calcium signaling, dopamine stimulation increased IP1 accumulation inAa DOP2-, Cq DOP2- andAg DOP2-expressing cells, and DAR antagonists inhibited IP1 signaling in a dose-dependent manner. In larval bioassays, DAR antagonists caused considerable mortality ofAn. gambiae larvae within 24 h post-exposure. Conclusions In vitro data reveal pleiotropic coupling ofAa DOP2 andCq DOP2 to Gαq and Gαs . In contrast, Ag DOP2 appeared to selectively couple to Gαq signaling. In vitro antagonist studies revealed general conservation in pharmacology between mosquito DARs. In vivo data suggest potential for DAR antagonist insecticides againstAn. gambiae . Sequence conservation among the DOP2 receptors from 15Anopheles species indicates utility of antagonists to control residual malaria transmission.Ag DOP2 Gαq -dependent signaling could be exploited forAn. gambiae control via pathway specific antagonists.